POTENCIAL ENERGÉTICO DOS RESÍDUOS SÓLIDOS DOMICILIARES DO MUNICÍPIO DE PONTA GROSSA, PR, BRASIL - Gomes, Simone (2014)
A major challenge, present in most Brazilian cities, it is the sustainable management of municipal solid waste (MSW). The final disposal of this waste, the way they are, i.e., without undergoing any form of treatment, brings a lot of problems, not just environmental but also social and mainly economic, because occurs loss of feedstock and also waste of the energy on this residues. One way to reuse this energy and reducing environmental impacts is the treatment of solid waste using the technology of controlled incineration with energy recovery. In this study was evaluated the energy potential of MSW of the Ponta Grossa/PR city from the incineration technology, being performed for that, two collections, the first producing a pattern residue and the second held at the municipal landfill. The dependent variables analyzed were the gravimetric characterization, proximate analysis and heating value. The gravimetric waste characterization of the second collection showed values close to the national average for recyclable waste (30% and 31.9%, respectively), values below the national average for organic matter and above for the tailings. In the immediate analysis, the content of fixed carbon was 0.03 to 0.09 kg kg-1, the volatile material of the samples of second collection ranged from 0.75 to 0.81 kg kg-1. And from the higher heating value of waste from both collections, 18,313 kJ kg-1 and 19,807 kJ kg-1, was estimated energy recovery. The electrical energy from MSW, in the current state, of the first collection would supply 51,534 homes in the city and the second collection, 55,500 residences. Considering the ideal scenario, with 100% of recycling, the energy recovered would still significant (18,199,095 MJ month-1), allowing the supply of 30,997 homes, 28% of the total households of Ponta Grossa.